Association of Genomic Alterations with the Presence of Serum Monoclonal Proteins in Chronic Lymphocytic Leukemia - Juan A. Piñeyroa; Irene López-Oreja; Ferran Nadeu; Ares Martínez-Farran; Juan Ignacio Aróstegui; Mónica López-Guerra; Juan Gonzalo Correa; Aleix Fabregat; Neus Villamor; Ines Monge-Escatín; Nil Albiol; Dolors Costa; et al. (Cells)
The presence of a monoclonal protein detected by serum immunofixation electrophoresis (sIFE) has been reported as an adverse prognostic factor in chronic lymphocytic leukemia (CLL). However, the genetic underpinning of this finding has not been studied. We retrospectively studied 97 CLL patients with simultaneous information on sIFE and genetic alterations detected by next-generation sequencing. sIFE was positive in 49 patients. The most common isotypes were IgG κ (27%) and bi/triclonal (25%). A +sIFE was associated with a higher number of mutated genes [median 2 (range 0–3) vs. 0 (range 0–2), p = 0.006], and a higher frequency of unmutated IGHV status (60 vs. 29%, p = 0.004). An IgM monoclonal protein was associated with TP53 mutations (36% in IgM +sIFE vs. 12% in non-IgM +sIFE or –sIFE, p = 0.04), and bi/triclonal proteins with NOTCH1 mutations (33% in bi/triclonal vs. 9% in monoclonal +sIFE or –sIFE, p = 0.04). These data suggest an association between a +sIFE and a higher mutational burden, and some monoclonal isotypes with specific mutations.